Changes in direct patient care from physiotherapy student to new graduate. (1st February 2021) - Stoikov, Susan; Gooding, Mark; Shardlow, Kassie; Maxwell, Lyndal; Butler, Jane; Kuys, Suzanne
ABSTRACT: Background : Clinical placements offer students an opportunity to provide direct patient care and are essential to develop safe and effective practitioners. It is unknown what changes in direct patient care activities are required as students transition to graduate physiotherapists. Objective : To determine the change in direct patient care activity from physiotherapy student to new graduate. Methods : Five hospitals provided clinical activity data from 412 physiotherapy students and 50 new graduate physiotherapists working in four physiotherapy clinical areas. Main Outcome Measures : Percentage of day spent in direct patient care, average occasions of service (OOS) per day and average length of one OOS (LOOS) for physiotherapy students and new graduates. Results : Students spent less time during their day providing direct patient care (24%, 95% confidence interval (CI) 19 to 29), performed fewer OOS (4.4, 95%CI 4.0 to 4.8) and had longer LOOS (18 min, 95%CI 13 to 23) compared to new graduates. This was consistent across all clinical areas. Conclusions : Physiotherapy student caseload is half that of a new graduate physiotherapist, with students taking longer to complete an OOS. Given this disparity in workload, active stakeholder engagement is essential to implement strategies that support and optimize the transition from student to graduate.